KOMPUTASI ENKRIPSI DAN DEKRIPSI MENGGUNAKAN ALGORITMA HILL CIPHER - Rara Wardhani; Siti Rahmah Nurshiami; Niken Larasati (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2022)
Hill Cipher is a symmetric cryptographic algorithm that can be used to encrypt and decrypt. Hill Cipher has several advantages including the key used to encrypt and decrypt is a square matrix of size n x n which has a multiplicative inverse because the inverse is the key used to decrypt. This study discusses the design of encryption and decryption program using with Java. The resulting program is capable of encrypting and decrypting with key 2 x 2, 3 x 3 , and 4 x 4.